Is Chinese Spring Festival a key point for glycemic control of patients with type 2 diabetes mellitus in China? - Xu, Huilin; Cao, Li; Li, Jun; Zhang, Fen; Wang, Weijie; Liang, Tongtong; Liu, Xiaohua; Fu, Chaowei (Frontiers in Public Health, 2022)
Objectives: To explore the long-term trend of fasting blood glucose (FBG) among urban patients with type 2 diabetes mellitus (T2DM) and impacts of the Chinese Spring Festivals on their glycemic control in urban China. Methods: The general information and longitudinal monitoring data of T2DM patients in Minhang District, Shanghai, China from December 15, 2006 to December 31, 2015 were collected. The FBG records were grouped into three periods: preholiday period (two months right before the Chinese Spring Festival), holiday period (from 28 December to 7 January of the lunar calendar year), and postholiday period (2 months after the Chinese Spring Festival).The Mann-Kendall trend test and Cochran-Armitage trend test were occupied to explore the long-term trend, and paired t-test and χ2 test were used to determine the differences in glycemic level and control rate between the preholiday and postholiday periods, respectively. Results: From 2007 to 2015, the glycemic control rate in patients with T2DM showed an upward trend (P < 0.001), and the FBG level showed a decreasing trend (P = 0.048). After the Chinese Spring Festivals, the glycemic control rate decreased significantly (P < 0.001) and the FBG level increased significantly (P < 0.001) compared those with the preholiday period. The incidence of hypoglycemia increased during holidays. Patients who aged 60 to 69 years old, was overweight or obesity, with hypertension, a disease duration < 3 years, or poor glycemic control in one previous year were more likely to be affected by the holiday. Conclusions: Chinese Spring Festival is a key point for glycemic control of patients with type 2 diabetes mellitus in China. Intensive holiday-specific diabetic healthcare needs to be further improved and community-based interventions should be developed and implemented to control the possible holiday effects.